Strategi Regulasi Emosi Personel Kepolisian Polda Jateng dalam Menghadapi Situasi Kerja Bertekanan Tinggi - Hanifah Arien Faradilla; Ummi Nabila Azaria; Aldila Dyas Nurfitri Penulis (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
Police work is considered a high-pressure profession because police personnel are required to handle social conflicts, unpredictable field situations, and professional demands while carrying out their duties. These conditions make emotion regulation an important ability for police officers to control emotional responses and maintain psychological stability in stressful work situations. This study aims to explore work pressure, emotional responses, and emotion regulation strategies among Central Java Regional Police personnel in dealing with high-pressure work situations. The study employed a descriptive qualitative approach using purposive sampling techniques. Participants consisted of three active police officers from the Central Java Regional Police. Data were collected through semi-structured interviews and analyzed using Miles and Huberman’s data analysis techniques, including data reduction, data display, and conclusion drawing. The findings revealed that work pressure experienced by police personnel originated not only from conflict situations in the field, but also from administrative demands, work responsibilities, long working hours, and professional expectations. These pressures generated emotional responses such as anxiety, fear, overthinking, emotional exhaustion, and boredom. The study found that emotion regulation strategies were carried out through simple daily activities, including positive thinking, self-affirmation, distraction, exercise, entertainment activities, remembering family, and social support from colleagues and family members. The findings indicate that emotion regulation plays an important role in helping police personnel maintain professionalism, control behavior, and strengthen psychological resilience while carrying out their duties.